ナンキョク ノ シャメン カコウフウ イキ ニオケル サスツルギ ヤ ドリフト ノ ショウモウ ニ ツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 上田, 豊; アゲタ, ユタカ; AGETA, Yutaka (国立極地研究所, 1972)
P(論文) The observations were made on net ablation of some of sastrugi and drifts (like barchanoids) in the area subjected to strong katabatic winds between 100 and 200 km inland from the Antarctic coast near Syowa Station in September and November, 1969 and in January, 1970 by means of the stake measurements. The net ablation of hard sastrugi during the period from November to January (mean 2.8 cm/month) was larger than that from September to November (mean 0.7 cm/month). The large amount of ablation from November to January may be attributed to the increase of solar radiation which accelerates sublimation-deflation on the surface of sastrugi. On the other hand, net ablation of soft sastrugi and drifts from September to November was larger than that from November to January. The large amount of ablation from September to November may be attributed to the strong erosion by the wind, since sastrugi and drifts were soft. Since they were hardened or flattened after erosion by the wind from September to November, the ablation from November to January was not larger than that from September to November. Since the rate of ablation at the top of sastrugi and drifts was higher than that at the surrounding surface in late spring and summer, and the bulk of yearly accumulation is deposited in autumn and winter, it can be said that surface irregularities are supposed to be built up in winter, then smoothed in summer. The best season for yearly stake measurements is considered to be the end of summer when the more accurate value of mean net accumulation may be expected since surface irregularities are less than any other season. Gow (1965) and WELLER (1969) gave some explanation for the higher rate of net ablation of sastrugi than the surrounding surface at the South Pole and Plateau Station. However, since the area of this report is located where the katabatic winds are strong as mentioned above, the situation is different from their case. According to the logarithmic increase of wind velocity, the top of sastrugi is ...